Glycan Quantitation Strategies Based on High Sensitivity NanoLC/MS - Staples, G. (Association of Biomolecular Resource Facilities, 2013)
Monoclonal antibodies (mAb), therapeutic proteins for treatments of cancers and immunological diseases, need detailed structural elucidation and improved analytics because of their biopharmaceutical presence. Inherently heterogeneous proteins, mAbs have various protein modifications, and the most important modification for these large glycoproteins is N-glycosylation on their Fc region. In this work, we compare several quantitative techniques; including microfluidic based on-line deglycosylation and integrated nanoLC/MS analysis of the released glycans, nanoLC/MS analysis of intact glycoprotein and/or glycoprotein fragments, as well as UHPLC-FLD analysis of off-line released derivatized glycans. We have utilized middle-up and bottom-up strategies for glycan quantitative analysis of humanized IgG1. In addition, we have also performed analysis of intact proteins such as RNAse B and prostate specific antigen and compared such results with released glycan strategy. Thorough glycan analysis was first performed using the mAb Glyco Chip to identify released free N-glycans, with structures extracted by molecular formula, and quantified by extracted ion chromatograms. IgG1 was also digested with IdeS to form Fc and Fab fragments. The ∼25kDa Fc fragment was analyzed using an HPLC-Chip/TOF MS system. For Fc region analysis, a maximum entropy deconvolution algorithm was used and the peak height of the deconvoluted spectra was used for high sensitivity relative quantitation of various glycoforms. An injection of as little as 5ng (30fmol) IgG1 generally was enough to generate high quality spectra. Complementary positive-ion and negative-ion modes on HPLC-Chip/MS with a make-up flow channel provided accurate identification and quantitation of PSA N-glycans. Two different PSA samples with different glycosylation patterns were compared, with about 30 glycans identified in each sample. HILIC UHPLC was used to separate the various glycan IgG isoforms. Glycan quantitation results based on HILIC separation paralleled the relative abundances of both the mAb Glyco Chip results and Fc region analysis.